2021
DOI: 10.3389/fpsyt.2021.701140
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in Recent Suicide Attempts: Altered Executive Function

Abstract: Background: Neuropsychological alterations can lead to inaccurate perception, interpretation, and response to environmental information, which could be a risk factor for suicide.Methods: Ninety-six subjects were recruited from the Psychiatry Department of the Araba University Hospital—Santiago, including 20 patients with a recent attempt and diagnosis of major depressive disorder (MDD) according to DSM-V, 33 MDD patients with history of attempted suicide, 23 non-attempter MDD patients, and 20 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Deficits in executive function can result in misunderstandings and inaccurate responses to internal and external environmental challenges; consequently, individuals may be easily overwhelmed and may engage in self-injury or suicidal ideation ( 26 ). Previous studies found executive function impairments among the HIV-negative population with suicidal ideation or suicidal behavior ( 27 29 ). Although limited evidence is available for HIV-positive individuals, one previous study suggested that suicidal ideation in this population might be a reflection of executive function deficits ( 30 ).…”
Section: Introductionmentioning
confidence: 92%
“…Deficits in executive function can result in misunderstandings and inaccurate responses to internal and external environmental challenges; consequently, individuals may be easily overwhelmed and may engage in self-injury or suicidal ideation ( 26 ). Previous studies found executive function impairments among the HIV-negative population with suicidal ideation or suicidal behavior ( 27 29 ). Although limited evidence is available for HIV-positive individuals, one previous study suggested that suicidal ideation in this population might be a reflection of executive function deficits ( 30 ).…”
Section: Introductionmentioning
confidence: 92%
“…51,52 One possible explanation for this finding could be that, even though executive functioning was not related to SB in this study, the previous literature did find that poorer executive functioning (defined as the neurocognitive function that organizes and directs behaviour and enables the perception, interpretation, and retrieval of, as well as response to environmental information) was associated with a pessimistic way of thinking about one's personal life. 25,53 Decision-making was one of the sub-domains of executive functioning that was consistently reported to be impaired in psychiatric populations with SB. [54][55][56] This might be associated with processing speed, visual memory, and psychomotor skills.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considering the BD patients in episodic and euthymic groups, the study results suggest that while BD patients are slower in terms of analysis, they may also be more impulsive than the general population, their mood state being a determinant for impulsiveness. Regarding to suicide attempts and neurocognitive functioning, Fernández-Sevillano et al (2021) studied cognition in patients that attempts to suicide and concluded that there were changes in the executive function performance when the episode was recent. However, in our sample, although 62% of patients in episode had been already suicide attempted, it was not recent.…”
Section: Discussionmentioning
confidence: 99%
“…We also emphasize that in our sample, in relation to the clinical group, we observed the occurrence of suicide. The literature shows that this is a variable that corresponds to cognitive impairment, according to the severity of the attempt and the time elapsed ( Fernández-Sevillano et al, 2021 ). As we did not control the type and possible sequelae, we emphasize that this is a feature limited to the present work, although in the Brazilian reality the legislation has a greater focus on considering the functional impact regardless of specificities such as, for example, a suicide attempt.…”
Section: Discussionmentioning
confidence: 99%